Regional competitiveness and training in Germany - Federico Foders (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
This paper analyses the German training system from the point of view of regional policy. The problems and prospects of the German system of first and further vocational training are addressed followed by an overview over macro and micro approaches to an empirical assessment of the regional impact of training measures. The paper concludes by proposing some reforms of current training policy in Germany.
Keywords: I21; J24; O15; 330; Schule; Duale Berufsausbildung; Betriebliche Bildungsarbeit; Regionalpolitik; Berufsbildungspolitik; Bildungsertrag; Deutschland